Rancang Bangun Mesin Uji Bending Untuk Material Komposit - Fikri Adi Kusuma; Fendi Tri Hartono; Ipung Kurniawan; Roy Aries Permana Tarigan (Accurate: Journal of Mechanical Engineering and Science, 2022)
The bending test machine for composite materials is a machine designed as material testing tool, especially composite materials. The objectives achieved are to design and manufacture a bending test machine as well as to test the composite material of epoxy resin and sugarcane powder based on the ratio of weight fractions. The machine design method uses the VDI 2222 method approach. From the method carried out, the results obtained from the design of the bending test machine using Solidwoks 2017. The design results of the bending test machine with dimensions of length 500 mm, width 500 mm, and height 1.400 mm, which consists of several main components including: frame; suppression system; and supports. The estimated time of the bending test machine production process takes 51,69 hours or 7 days. The results of the composite material test resulted in the bending strength of the 100% resin weight fraction of 67,71 Mpa and the 50% sugarcane powder weight fraction of 33,74 Mpa.